Nilai-Nilai Kepemimpinan Dalam Perspektif Ajaran Hindu - Hemamalini, Kadek (Dharma Duta, 2019)
Leaders are people who are tasked to guide and direct the people they lead, a leader has a very heavy duty in directing the community he leads. A good leader is a leader who is capable of carrying out all duties and obligations as a leader and is able to direct the community he leads. In Hinduism itself there are goals of Hindu leadership which aim to form a good, strong, clean, and authoritative state leadership and Hindu leadership functions which consist of functions as motivational factors, as creative factors, as integrative factors, as sublimative or transformative factors, and as an inspiring factor. The criteria for leadership in Hinduism is to have a basic principle that is a guide in leading